Kinetics of Leptospira interrogans Infection in Hamsters after Intradermal and Subcutaneous Challenge - Coutinho, Mariana L. (PLoS Negl Trop Dis, 2014)
BACKGROUND: Leptospirosis is a zoonosis caused by highly motile, helically shaped bacteria that penetrate the skin and mucous membranes through lesions or abrasions, and rapidly disseminate throughout the body. Although the intraperitoneal route of infection is widely used to experimentally inoculate hamsters, this challenge route does not represent a natural route of infection. METHODOLOGY/PRINCIPAL FINDINGS: Here we describe the kinetics of disease and infection in hamster model of leptospirosis after subcutaneous and intradermal inoculation of Leptospira interrogans serovar Copenhageni, strain Fiocruz L1-130. Histopathologic changes in and around the kidney, including glomerular and tubular damage and interstitial inflammatory changes, began on day 5, and preceded deterioration in renal function as measured by serum creatinine. Weight loss, hemoconcentration, increased absolute neutrophil counts (ANC) in the blood and hepatic dysfunction were first noted on day 6. Vascular endothelial growth factor, a serum marker of sepsis severity, became elevated during the later stages of infection. The burden of infection, as measured by quantitative PCR, was highest in the kidney and peaked on day 5 after intradermal challenge and on day 6 after subcutaneous challenge. Compared to subcutaneous challenge, intradermal challenge resulted in a lower burden of infection in both the kidney and liver on day 6, lower ANC and less weight loss on day 7. CONCLUSIONS/SIGNIFICANCE: The intradermal and subcutaneous challenge routes result in significant differences in the kinetics of dissemination and disease after challenge with L. interrogans serovar Copenhageni strain Fiocruz L1-130 at an experimental dose of 2×10(6) leptospires. These results provide new information regarding infection kinetics in the hamster model of leptospirosis.